Self-assessment: The role of the social environment - Armin Falk; Fabian Kosse; Hannah Schildberg-Hörisch; Florian Zimmermann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
This study presents descriptive and causal evidence on the role of the social environment in shaping the accuracy of self-assessment. We introduce a novel incentivized measurement tool to measure the accuracy of self-assessment among children and use this tool to show that children from high socioeconomic status (SES) families are more accurate in their self-assessment, compared to children from low SES families. To move beyond correlational evidence, we then exploit the exogenous variation of participation in a mentoring program designed to enrich the social environment of children. We document that the mentoring program has a causal positive e ffect on the accuracy of children's self-assessment. Finally, we show that the mentoring program is most e ffective for children whose parents provide few social and interactive activities for their children.
Keywords: D03; C21; C91; I24; 330; Self-Assessment; Beliefs; Experiments; Randomized Intervention; Children